Polarity gene alterations in pure invasive micropapillary carcinomas of the breast - Gruel, Nadège (BioMed Central, 2014)
INTRODUCTION: Pure invasive micropapillary carcinoma (IMPC) is a special type of breast carcinoma characterised by clusters of cells presenting polarity abnormalities. The biological alterations underlying this pattern remain unknown. METHODS: Pangenomic analysis (n = 39), TP53 (n = 43) and PIK3CA (n = 41) sequencing in a series of IMPCs were performed. A subset of cases was also analysed with whole-exome sequencing (n = 4) and RNA sequencing (n = 6). Copy number variation profiles were compared with those of oestrogen receptors and grade-matched invasive ductal carcinomas (IDCs) of no special type. RESULTS: Unsupervised analysis of genomic data distinguished two IMPC subsets: one (Sawtooth/8/16) exhibited a significant increase in 16p gains (71%), and the other (Firestorm/Amplifier) was characterised by a high frequency of 8q (35%), 17q (20% to 46%) and 20q (23% to 30%) amplifications and 17p loss (74%). TP53 mutations (10%) were more frequently identified in the amplifier subset, and PIK3CA mutations (4%) were detected in both subsets. Compared to IDC, IMPC exhibited specific loss of the 6q16-q22 region (45%), which is associated with downregulation of FOXO3 and SEC63 gene expression. SEC63 and FOXO3 missense mutations were identified in one case each (2%). Whole-exome sequencing combined with RNA sequencing of IMPC allowed us to identify somatic mutations in genes involved in polarity, DNAH9 and FMN2 (8% and 2%, respectively) or ciliogenesis, BBS12 and BBS9 (2% each) or genes coding for endoplasmic reticulum protein, HSP90B1 and SPTLC3 (2% each) and cytoskeleton, UBR4 and PTPN21 (2% each), regardless of the genomic subset. The intracellular biological function of the mutated genes identified by gene ontology analysis suggests a driving role in the clinicopathological characteristics of IMPC. CONCLUSION: In our comprehensive molecular analysis of IMPC, we identified numerous genomic alterations without any recurrent fusion genes. Recurrent somatic mutations of genes participating in cellular polarity and shape suggest that they, together with other biological alterations (such as epigenetic modifications and stromal alterations), could contribute to the morphological pattern of IMPC. Though none of the individual abnormalities demonstrated specificity for IMPC, whether their combination in IMPC may have a cumulative effect that drives the abnormal polarity of IMPC needs to be examined further with in vitro experiments.